Aggregate availability of doctors in India: 2014-2030 - Basant Potnuru (Wolters Kluwer Medknow Publications, 2017)
Background: The current belief of availability of doctors in India is based on the registration stock of doctors accumulated since the early 20th century. This has not been adjusted to attrition of the strength occurring due to retirement, emigration, etc. Objectives: To estimate the number of practicing doctors currently available in India and will be available in 2030 after adjustments made for attrition of the stock. Methods: The paper used Medical Council of India's historical data (1960-2015) on registration stock of doctors obtained from the Indian medical registers available on its website and other data on emigration of doctors accessed from Organization for Economic Cooperation and Development and destination country sources. Results: The paper found that there were only 4.8 practicing doctors per 10,000 population available in India in 2014, in contrast to the belief of having 7 doctors per 10,000 people. Rest of the registered doctors have either retired or emigrated from the country to practice abroad. It is estimated that the country would be able to achieve a ratio of about 6.9 practicing doctors per 10,000 people only by 2030. Conclusion: Given these findings of the current availability of doctors per 10,000 people and their growth prospects over the next 15-year period, it looks like an impossible task to achieve even a moderate doctor-population ratio of 1:1000 by 2030. Therefore, a genuine commitment to provide equitable healthcare to the rural population must innovate and experiment a special cadre of practitioners for rural areas on a pan-India basis.